Work the Root: Black Feminism, Hoodoo Love Rituals, and Practices of Freedom. (9th December 2016) - Stewart, Lindsey
Abstract : In "Post‐Liberation Feminism, " Ladelle McWhorter raises the question of what practices will be helpful to further feminist goals if we are no longer in a state of domination, but are still oppressed. McWhorter finds resources in Michel Foucault's concept of "practices of freedom" to begin to answer this question. I build upon McWhorter's insight while recalling Angela Davis's Blues Legacies and Black Feminism : namely, that sexual love, as conceived in hoodoo and the blues, became a terrain upon which newly emancipated blacks worked out what their newfound freedom meant. In this essay, I consider what practices of freedom would look like within a life‐giving nexus of hoodoo, blues, and sexual love. Not only does the image of the hoodoo woman, prevalent within the blues, emerge through an interaction of race, class, region, gender, sexuality, and spiritualty, but analyzing sexual love within this hoodoo–blues coupling will help us track how sexual love was transformed into a practice of freedom. I will argue that sexual love within this hoodoo–blues coupling reveals an important dimension of emancipatory work that both defies categorization as resistance and is crucial to the development of capacities for resistance.